Proceedings of the 18th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2015
DOI: 10.1145/2675133.2675144
|View full text |Cite
|
Sign up to set email alerts
|

Crowds on Wall Street

Abstract: In crowdsourced systems, it is often difficult to separate the highly capable "experts" from the average worker. In this paper, we study the problem of evaluating and identifying experts in the context of SeekingAlpha and StockTwits, two crowdsourced investment services that are encroaching on a space dominated for decades by large investment banks. We seek to understand the quality and impact of content on collaborative investment platforms, by empirically analyzing complete datasets of SeekingAlpha articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Various techniques have been applied in machine learning approaches. For example, Wang et al [33] used the SVM, naive Bayes, and decision trees to classify StockTwits data into "bullish" and "bearish" and discovered that the SVM performed the best. Subsequently, models combined with lexicon-based techniques were established [34].…”
Section: Background and Related Studiesmentioning
confidence: 99%
“…Various techniques have been applied in machine learning approaches. For example, Wang et al [33] used the SVM, naive Bayes, and decision trees to classify StockTwits data into "bullish" and "bearish" and discovered that the SVM performed the best. Subsequently, models combined with lexicon-based techniques were established [34].…”
Section: Background and Related Studiesmentioning
confidence: 99%
“…In this research context, among the recent contributions in the literature, Li et al (2014) and index levels, model using sentiment analysis outperform the bag-of-words model in both validation and testing sets and that there is a minor difference between the models using the two different dictionaries. Wang et al (2015) work on sentiment analysis retrieved from SeekingAlpha articles and StockTwits messages, two social media platforms, and analyze their correlation with S&P 500 Index movements, finding the former has better explanatory power, even though sentimentbased investment strategies have generally poor performances. They use a dictionary-based approach for SeekingAlpha analysis, relying on LM, and a supervised ML approach for StockTwits, using labels assigned directly by users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Typically, investor sentiment on social media is extracted from user posts and aggregated at the asset level (Das and Chen, 2007), and it has been widely used to demonstrate its predictability of financial market performance, such as the trends of Dow Jones or S&P 500 Index (Bollen et al, 2011;Zheludev et al, 2014;Piñeiro-Chousa et al, 2016), stock price movement (Oh and Sheng, 2011;Zhang et al, 2012;Wang et al, 2015), abnormal returns (Ranco et al, 2015;Deng et al, 2018), earning surprises (Chen et al, 2014;Bartov et al, 2018), trading volume (Tan and Tas, 2021), and market volatility (Hou and Tripathi, 2015;Audrino et al, 2020). However, mixed evidence is also reported that investor sentiment does not have strong predictability of stock returns (Oliveira et al, 2013;Kim and Kim, 2014), or the magnitude of the effect is economically small (Nofer and Hinz, 2014).…”
mentioning
confidence: 99%